The Implementation of Islamic Education Teaching at Inclusive Schools in Samarinda, East Kalimantan - Elnurianda, Fitra; Fauzan, Umar; Hamzah, Syeh Hawib (Madania: Jurnal Kajian Keislaman, 2018)
Education is an individual right for all citizens, including children with special needs. The objective of the research is a qualitative research using phenomenology approach conducted at elementary schools (SD) in Samarinda; is to describe the implementation of Islamic education teaching at inclusive schools in Samarinda. This research SD Fastabiqul Khairat Samarinda, SD Bunga Bangsa Samarinda, and State Elementary School (SDN) 016. The techniques used in data collection are observation, interview, and documentation. The data was analyzed by using the interactive model by Miles and Huberman. The finding of this research reveals that the implementation of Islamic education teaching at inclusive schools in Samarinda requires several adjustments in teaching planning, implementation process, and learning evaluation. Those adjustments were created in the form of special class, by providing specific time allocation, preparing different teaching materials, applying different teaching methods, and using a mixed approach.